Spatial-temporal genome damaging in the blue crab Cardisoma guanhumi as ecological indicators for monitoring tropical estuaries - Falcão, C. B.R.; Pinheiro, M. A.A. [UNESP]; Torres, R. A.; Adam, M. L. (Elsevier, 2020)
In this study, to better our understanding of the current state of conservation of Cardisoma guanhumi and its habitats, we evaluated the potential spatio-temporal genomic damage of this species across five estuaries in Brazil. The experiment was performed over two consecutive years, and the sampling was performed in the winter and summer seasons. Two genetic tests — micronucleus test and comet assay — were used to quantify the DNA damage. Unlike in the summers and in the winter of 2013, in the winter of 2012 a significant increase was noted in the frequency of micronucleated cells and genomic damage index. The occurrence of genomic damage coincided with the arrival of the harsh winter of 2012 as the water sourced from the coastal rivers significantly affected the estuarine species under study. Our results confirmed that this species was resilient to the atypical climatic conditions, which facilitated the generation of excessive waste.
Keywords: Blue crab; Comet assay; Estuaries; Genomic damage; Micronucleus test